Written Monument "al-Qawanin" in the Mamluk-Kipchak language: textological analysis - Aubakirova К Қ; Mustafayeva А А (Journal of Oriental Studies, 2016)
The article considers the textological analysis of written monument al-Kavanin" written in the Mamluk-Kipchak language during the authority of Mamluks